2021
DOI: 10.1371/journal.ppat.1009514
|View full text |Cite
|
Sign up to set email alerts
|

Host microbiota can facilitate pathogen infection

Abstract: Animals live in symbiosis with numerous microbe species. While some can protect hosts from infection and benefit host health, components of the microbiota or changes to the microbial landscape have the potential to facilitate infections and worsen disease severity. Pathogens and pathobionts can exploit microbiota metabolites, or can take advantage of a depletion in host defences and changing conditions within a host, to cause opportunistic infection. The microbiota might also favour a more virulent evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 192 publications
(213 reference statements)
0
85
0
Order By: Relevance
“…A plethora of recent studies have forwarded the notion that diverse microbial symbionts, the microbiome, have a central and largely positive role in the health of animals (Bordenstein and Theis 2015) and plants (Porras-Alfaro and Bayman 2011). Although microbiome control of disease and pests is increasingly sought (Scheuring and Yu 2012;Kepler et al 2017;Schlatter et al 2017;Syed Ab Rahman et al 2018) and may slow the evolution of resistance to antibiotics (Sommer and Dantas 2011;Tosh and McDonald 2012) or reduce dependence on environmentally damaging chemicals (Xue et al 2015), recent empirical and theoretical results provide a counterpoint to a view that microbes and their hosts necessarily coevolve to mutualistic states (Antwis et al 2015;Jani and Briggs 2018;Stevens et al 2021). Competitive interactions between symbionts (Hoeksema and Kummel 2003;Nelson and May 2020) and between parasites (Bell et al 2006;Barrett et al 2011;Alizon et al 2013) may cause a shift to less beneficial communities (Johnson et al 1997) and selection on greater parasite virulence (Moran and Sloan 2015;Nelson and May 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of recent studies have forwarded the notion that diverse microbial symbionts, the microbiome, have a central and largely positive role in the health of animals (Bordenstein and Theis 2015) and plants (Porras-Alfaro and Bayman 2011). Although microbiome control of disease and pests is increasingly sought (Scheuring and Yu 2012;Kepler et al 2017;Schlatter et al 2017;Syed Ab Rahman et al 2018) and may slow the evolution of resistance to antibiotics (Sommer and Dantas 2011;Tosh and McDonald 2012) or reduce dependence on environmentally damaging chemicals (Xue et al 2015), recent empirical and theoretical results provide a counterpoint to a view that microbes and their hosts necessarily coevolve to mutualistic states (Antwis et al 2015;Jani and Briggs 2018;Stevens et al 2021). Competitive interactions between symbionts (Hoeksema and Kummel 2003;Nelson and May 2020) and between parasites (Bell et al 2006;Barrett et al 2011;Alizon et al 2013) may cause a shift to less beneficial communities (Johnson et al 1997) and selection on greater parasite virulence (Moran and Sloan 2015;Nelson and May 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Competitive interactions between symbionts (Hoeksema and Kummel 2003;Nelson and May 2020) and between parasites (Bell et al 2006;Barrett et al 2011;Alizon et al 2013) may cause a shift to less beneficial communities (Johnson et al 1997) and selection on greater parasite virulence (Moran and Sloan 2015;Nelson and May 2017). Certainly, the ecological and evolutionary consequences of the "tangled bank" of multiple microbial interactions within hosts are poorly understood but important to sustainable use of defensive symbionts in disease control (Betts et al 2016;Busby et al 2016;King et al 2016;Koskella et al 2017;Toju 2018;Stevens et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host microbiome can enhance pathogen infection by modifying the within-host environment interacting with the pathogen or driving the pathogen ( 80 ). In the case of pathogenic viruses, some microbiomes are associated with higher susceptibility to infection.…”
Section: Microbiome-mediated Enhancement Of Viral Infectionsmentioning
confidence: 99%
“…Another example is given by Round et al (2011), where it was shown that Bacteroides fragilis acts via the toll-like receptor (TLR)2 on T helper cells to ensure microbial symbiosis. Deletion of TLR2 specifically on T helper cells lead to activation of an anti-microbial response that limits B. fragilis colonization (for review of more host-microbe interactions by which microbes establish competitive advantages within the host's gut microbiota, see Round et al, 2011;Stevens et al, 2021). Likewise, some pathogenic species have been shown to benefit from the host immune response eliminating their competitors.…”
Section: Host-microbe Interactionsmentioning
confidence: 99%